2022
DOI: 10.3390/ph15050545
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Multitarget Anti-Alzheimer Drug Discovery Landscape: A Bibliometric Analysis

Abstract: Multitarget anti-Alzheimer agents are the focus of very intensive research. Through a comprehensive bibliometric analysis of the publications in the period 1990–2020, we have identified trends and potential gaps that might guide future directions. We found that: (i) the number of publications boomed by 2011 and continued ascending in 2020; (ii) the linked-pharmacophore strategy was preferred over design approaches based on fusing or merging pharmacophores or privileged structures; (iii) a significant number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Conversely, simultaneous modulation of several targets (multitarget approach) has emerged as a very promising option to efficiently cope with the AD pathological network [ 35 ]. Very intensive research has been done in the last decade for the development of different classes of multitarget agents, i.e., single molecules designed to hit several biological targets [ 36 ]. However, much less attention is being given to the development of combination therapies, i.e., combinations of two or more drugs each one hitting a different biological target.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, simultaneous modulation of several targets (multitarget approach) has emerged as a very promising option to efficiently cope with the AD pathological network [ 35 ]. Very intensive research has been done in the last decade for the development of different classes of multitarget agents, i.e., single molecules designed to hit several biological targets [ 36 ]. However, much less attention is being given to the development of combination therapies, i.e., combinations of two or more drugs each one hitting a different biological target.…”
Section: Discussionmentioning
confidence: 99%
“… General structures ( A , B ) of the potent MARK4 inhibitors (IC 50 < 1 µM) described [ 14 , 15 , 16 , 17 , 18 , 19 ]. The common feature of pyrimidine 2,4,5-trisubstituted ( A ) or 2-substituted-4,5-cyclic ( B ) in blue, the favorable substituents in rectangular frames.…”
Section: Figurementioning
confidence: 99%
“…It is supposed that the clinical failure of 5-HT 6 R agents is a consequence of the fact that those anti-AD drug candidates have been designed as single-target molecules, whereas such a complex disease as AD involves many different signaling pathways that form the pathological network [ 15 ]. Hence, selecting just one target may indeed lead to insufficiency [ 16 ]. Moreover, multidirectional molecules may have a more predictable pharmacokinetic profile than combined therapy with two or more single-target drugs [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional systematic evaluation and meta-analysis, bibliometric analysis can reveal the present situation and the evolution of research topics from a more systematic and intuitive level. In recent years, some researchers have combed and analyzed the literature on AD-related research from the perspective of bibliometrics, for example, the brain energy metabolism disorder mechanism of AD [ 18 ], publishing trends in AD research [ 19 , 20 ], drug research with regard to AD [ 21 , 22 , 23 ], genetic research on AD [ 24 ], and so on. Specifically, through analyzing the literature from 2000 to 2020, Y.-H. Du et al found that brain energy disorder plays a central role in the occurrence and development of AD.…”
Section: Introductionmentioning
confidence: 99%